A prospective cross-sectional study of thyroid dysfunction in transfusion- dependent beta-thalassemia patients - Channanayaka Chandrashekhar,; Manovihari Vuyyuru,; Prajwala Hassan Vasudev,; George Mathew Panachiyil,; Tirin Babu, (Indian Journal of Child Health, 2021)
Objective: The objective of the study was to determine the hospital-based prevalence of thyroid dysfunction in transfusion-dependent beta-thalassemia in children and to study the correlation between serum ferritin levels and thyroid functions. Methods: This prospective cross-sectional study in transfusion-dependent thalassemia patients was conducted in the department of pediatrics of a teaching hospital in India. General and systemic examinations were done and recorded and hemoglobin (Hb)%, thyroid-stimulating hormone (TSH), T3, T4, free thyroxin 4 (FT4), serum ferritin, and anti-thyroid peroxidase (TPO) levels were estimated in the laboratory. Initially, the estimation of Hb, TSH, T3, T4, and serum ferritin was done for all the study participants. Later, the specific values of FT4 and anti-TPO were estimated in study participants with high TSH values. Results: Fifty beta-thalassemia children aged between 3 and 18 years were chosen in this study. The prevalence of subclinical hypothyroidism was 6% and no cases of clinical or central hypothyroidism were found. The mean serum ferritin level was 2671 ± 1592 ng/ml; however, no positive correlation between serum ferritin and TSH values was seen. Conclusion: In thalassemia patients, the thyroid failure usually occurs by the second decade of their life. It is important that all beta-thalassemia children should undergo annual screening of thyroid functions in addition to detection of their serum ferritin levels.